BANJIR BANDANG SEBAGAI KONSEKUENSI KERUSAKAN HUTAN: ANALISIS PENEGAKAN HUKUM LINGKUNGAN DI SUMATERA - Asep Slamet; Timbo Mangaranap Sirait (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2026)
Massive forest degradation in Sumatra has increased ecological vulnerability and intensified the frequency of flash floods. These disasters are not solely caused by extreme rainfall but are closely linked to the loss of forest functions in upstream watershed areas due to illegal logging and uncontrolled land-use change. This study examines the causal relationship between forest degradation and flash floods and evaluates the effectiveness of environmental law enforcement in addressing such damage. The research employs a normative juridical method with statutory and conceptual approaches, using data from legal regulations, court decisions, and institutional reports. The findings show that although Indonesia has a relatively comprehensive environmental legal framework, its enforcement remains suboptimal. Weak supervision, inconsistent sanctions, and the lack of deterrent effects on business actors allow forest degradation to persist. Strengthening firm and consistent environmental law enforcement is therefore essential to prevent ecological disasters and protect the public’s right to a good and healthy environment.